2018
DOI: 10.1080/09540105.2018.1483900
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fish matrix on colloidal gold immunochromatographic assay of antibiotics: the source of interference and removal method

Abstract: The matrix effect is a serious problem for the immunoassay of antibiotic residues, which greatly restricts its real application in fishery products as well as other foodstuffs. Till now the related information on the colloidal gold immunochromatographic assay (GICA) is still limited. Therefore, five species of fish as samples, and the interference of main matrix components on the analysis of ciprofloxacin was investigated. Some water-soluble proteins were demonstrated to have significant affluence on GICA. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some studies have indicated that porphyrin as the host molecule could recognize amino acids, 27,28 and this may imply the possible interaction between porphyrin and some proteins such as antibodies and enzymes, and therefore result in the interference to the ELISA. Moreover, in our previous work 29 magnesium was observed able to affect the antibody–antigen recognition significantly, maybe by its interaction with the specific site (Fab fragment) of antibodies; considering the rich content of magnesium in chlorophyll, 30 such a magnesium‐induced interference may also contribute to the matrix effect investigated here.…”
Section: Resultsmentioning
confidence: 64%
“…Some studies have indicated that porphyrin as the host molecule could recognize amino acids, 27,28 and this may imply the possible interaction between porphyrin and some proteins such as antibodies and enzymes, and therefore result in the interference to the ELISA. Moreover, in our previous work 29 magnesium was observed able to affect the antibody–antigen recognition significantly, maybe by its interaction with the specific site (Fab fragment) of antibodies; considering the rich content of magnesium in chlorophyll, 30 such a magnesium‐induced interference may also contribute to the matrix effect investigated here.…”
Section: Resultsmentioning
confidence: 64%
“…This phenomenon is called the matrix effect and has been mentioned in previous articles. [16][17][18] It is recommended that this type of intelligent packaging be designed and used to show other antibiotic residues in poultry meat.…”
Section: Discussionmentioning
confidence: 99%